Payback: Effects of relationship and cultural norms on reciprocity. Issue 3 (9th June 2014) - Jung, Younbo; Hall, Jeff; Hong, Renyi; Goh, Tiffany; Ong, Natalynn; Tan, Nathanael
<x xml:space="preserve">Abstract</x> This experimental investigation explores differences in reciprocal norms between friends and strangers and the effects of culture on reciprocity. Based on altruistic and strong reciprocity theories, a hybrid trust‐dictator game tested the influence of relationship (i.e. friends vs. strangers), treatment (i.e. positive vs. negative) and culture (i.e. collectivistic vs. individualistic) on reciprocation. The results show that participants reciprocated more positively when treated positively in general. However, the results demonstrate intercultural differences in reciprocal norms, specifically in the negative treatment condition. Participants from the individualistic culture provided stronger punishment to the norm violator, compared to participants from the collectivistic culture. We discuss implications of the impact of relationship and culture on reciprocation with respect to the olive branch response.